Corporate integrity and leadership: a case study of a Government Linked Company in Malaysia / Hanafiah Hasin … [et al.] - Hasin, Hanafiah; Rahim, Azlina; Nordin, Enylina; Hussain, Wan Shafizah; Alias, Nor Ashikin; Said, Jamaliah (Faculty of Accountancy, 2019)
Malaysia is one of many countries around the world that are besieged with negative perception of being corrupt. As reported by Transparency International, Malaysia is the sixty-one least corrupt nation out of one-hundred seventy-five countries, according to the 2018 Corruption Perceptions Index. Therefore, there is an urgent need for Malaysian public and private sectors to undertake the voluntary action to clear the perception of the publics towards Malaysian country. Since, the leader play an important role in the organisational success. Therefore, this study aims to assess the roles played by the leader toward the implementation of corporate integrity in the firms. This paper focuses on the leadership influence towards the success of corporate integrity implementation in the government-linked company (GLC). Data were collected via questionnaires from hundred executives and managers of a GLC in Malaysia. The data were collected based on the respondents’ perception on the leadership elements of integrity by using five-point Likert scale. Our findings confirmed that the case firm implemented a good corporate integrity practice in the firm. Consistent with the literature, the findings suggest that managing ethically is considered as an essential leadership competency. In addition, the senior managers are seen as a role model for the leadership. Finally, this paper hope to provide detailed documentation on the corporate integrity implementation to rebuild the good image of country of Malaysia.